Chicken Coccidiosis in Central Java, Indonesia: A Recent Update - Penny Humaidah Hamid; Yuli Purwandari Kristianingrum; April Hari Wardhana; Sigit Prastowo; Liliana Machado Ribeiro da Silva (Veterinary Medicine International)
Avian coccidiosis is a huge problem worldwide. Heavily infected animals that show severe clinical signs and coccidiostat resistance are causing important economic losses. The present study aimed to update the recent cases of coccidiosis in Central Java, Indonesia, and to show the importance of the disease in the region. A total of 699 samples were obtained from different chicken breed. Different Eimeria species were detected in 175 individuals (25.04%). Three different groups of chicken breed were considered: local chicken (autochthonous chickens of Sentul and Jawa), commercial broiler, and layer. Broiler chickens showed the highest prevalence of infection (34%), followed by layer (26.26%) and local chickens (10.45%). Mild to severe clinical signs of avian coccidiosis were observed in 42% of the infected animals, while 58% of the infected animals showed no clinical signs other than low feed conversion rates. Seven different Eimeria species were identified: E. tenella was the most prevalent (43.3%), followed by E. maxima (26.3%), E. necatrix (15.7%), E. acervulina (8%), E. praecox (3.1%), E. mitis (2.2%), and E. brunetti (1.3%). Coinfections with several Eimeria species were diagnosed. With this study we found massive usage of coccidiostat in the region even though its usage cannot guarantee coccidiosis-free chicken production.